Visualisasi Letak Geografis Provinsi Di Indonesia Berbasis Augmented Reality Untuk Siswa SD - Suharsono Bantun; Jayanti Yusmah Sari; Qammaddin Qammaddin; Rahmat Karim (INFORMAL: Informatics Journal, 2021)
The learning implementation in the subject of ¬social science¬, especially the topic of Indonesia's geographical location at SD Negeri 99 Pongrakka is still carried out in a classical way, namely using the lecture method with learning media in the form of depictions on the blackboard or just observing pictures through textbooks. These methods make the learning process less interesting and seem passive because there is no direct interaction between the topic and the students. To create interactive learning, we propose the development of learning media by utilizing Augmented Reality technology. The system proposed in this study can display the geographical location of the province in 3 dimensions by means of the user pointing the marker at the camera then the camera detects the marker and the object will be displayed directly on the monitor screen according to the marker used. After testing the system based on the Software Requirement Specification, it was able to be concluded that the application of visualizing the geographical location of the province based on Augmented Reality could not only make learning more interactive but also more interesting, so that it could be used as an option for learning methods.